Connecting with Citizens: The Rationale for SAIs’ Existence in the 21st Century - Fayyaz, Aamir (Journal of Public Policy Practitioners, 2024)
The 21st century offers unique opportunities and challenges for public sector institutions. Technology has increased the choices available to the citizens in their personal and private lives and, consequently, there is immense pressure on public institutions to deliver with enhanced efficiency and effectiveness. Generally, it is the responsibility of public audit institutions, commonly called the Supreme Audit Institutions (SAIs), to provide independent reports to the legislatures on the adherence of government departments to regulatory and performance benchmarks. SAIs, like other service delivery institutions, are accountable to the ultimate stakeholders: the citizens. Currently, however, their engagement with the latter is somewhat sub-optimal. While some SAIs have engaged the citizens at various levels, the overall public audit community has a long way to go. SAIs need to connect with the citizens in a meaningful manner and the latter’s involvement in audit tasks should be consistent throughout the audit cycle, that is, from planning to reporting. For SAIs, to justify their existence in today’s world, this would be a respectable and dignified approach to adopt.